2018
DOI: 10.1186/s13104-018-3314-9
|View full text |Cite
|
Sign up to set email alerts
|

Where to from here? A quality improvement project investigating burns treatment and rehabilitation practices in India

Abstract: ObjectiveTo describe the capacity of the Indian healthcare system in providing appropriate and effective burns treatment and rehabilitation services.ResultsHealth professionals involved in burns treatment or rehabilitation at seven hospitals from four states in India were invited to participate in consultative meetings. Existing treatment and rehabilitation strategies, barriers and enablers to patient flow across the continuum of care and details on inpatient and outpatient rehabilitation were discussed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…They showed that implementing prevention strategy results in significant improvement, especially in primary and secondary prevention. Also, some other studies noted that weak performance of burn wards is not due to hospital performance or severity of injuries, but it is mostly due to society’s awareness about burn, primary measures and prevention [13]. A study by Hodgins et al has also emphasized awareness of burns [21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They showed that implementing prevention strategy results in significant improvement, especially in primary and secondary prevention. Also, some other studies noted that weak performance of burn wards is not due to hospital performance or severity of injuries, but it is mostly due to society’s awareness about burn, primary measures and prevention [13]. A study by Hodgins et al has also emphasized awareness of burns [21].…”
Section: Discussionmentioning
confidence: 99%
“…Various unplanned visits and ignoring sanitary codes by patients’ families, also increase the secondary infections in hospitalised burn patients. Jagnoor et al showed that lack of society’s awareness on basic burn services can reduce desired consequences [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations